A DESCRIPTIVE STUDY ON THE TEACHER TALK AT EYL CLASSROOM - Setiawati, Liani (Indonesian Journal of Applied Linguistics, 2012)
Abstract: The use of constructive teacher talk (TT) is very important and effective in scaffolding young learners to improve their skill in target language. Nevertheless, there is an argument that too much teacher talk can even decrease students’ motivation. The present study tries to reveal the suitable amount and the students’ perception of teacher talk. Apart from that, there is an attempt to find out the features of teacher talk, the frequency of either display and referential questions or teachers’ assessments and ways in giving feedback. This descriptive study is conducted to find out how teachers make use of their teacher talk naturally in classroom settings. To gain deeper insight and understanding, both qualitative and quantitative research design were employed. The qualitative data were obtained through direct observation and teachers – students’ interview. Moreover, the teachers – students’ questionnaire, video recording and field notes also added significant value towards the findings of this study. Quantitative data, on the other hand, were gained from the calculation of students’ questionnaire scores which are represented in percentage. Both qualitative and quantitative data were coded, categorized, interpreted, descriptively described and finally displayed in the form of tables. The research findings show that despite the teacher talk’s capability to be good model for young learners,  most students found the class more motivating, interesting, and challenging when the teachers minimized their teacher talk  and made use not only more constructive teacher talk but also  interesting activities. In conclusion, since teacher talk serves not only as a medium to achieve young learners’s learning objectives but also as a tool to build better dynamic interaction between teacher and students in classroom settings, it is advisable for all EFL teachers to improve their effective constructive talk towards their students.   Key words: SLA, TT (Teacher Talk), TTT (Teacher Talk Time), discourse Analysis, code switching, conversational analysis, ST (Students Talk) , STT (Student Talk Time)